2019
DOI: 10.1177/1082013219877267
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes expression in viable but non-culturable state of Listeria monocytogenes in fish meat

Abstract: This study aimed to evaluate the fate of Listeria monocytogenes in water microcosm and rainbow trout fillet under salinity stress of 0% and 30% NaCl at refrigerator temperature (4 ± 2 ℃). Bacterial culturability was studied by standard culture and colony count method. Reverse transcription-PCR (RT-PCR) of 16 S rRNA gene was used to detect viability of non-culturable bacteria. Also, the qualitative expression of pathogenic genes ( hly and inlA) was studied using RT-PCR. The results showed that bacteria in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These results proved the usefulness of RT‐PCR to detect VBNC bacteria which is based on the short half‐life of RNA. Our results are in line with previous studies reporting the successful use of RT‐PCR for detection of different bacteria (Casasola‐Rodríguez et al, 2018; Coutard, Pommepuy, Loaec, & Hervio‐Heath, 2005; Y. Liu et al, 2008; Zolfaghari et al, 2020). In recent studies, the other methods including direct viable count, staining, and molecular biological methods have been used for differentiation between viable and dead cells (Schottroff et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results proved the usefulness of RT‐PCR to detect VBNC bacteria which is based on the short half‐life of RNA. Our results are in line with previous studies reporting the successful use of RT‐PCR for detection of different bacteria (Casasola‐Rodríguez et al, 2018; Coutard, Pommepuy, Loaec, & Hervio‐Heath, 2005; Y. Liu et al, 2008; Zolfaghari et al, 2020). In recent studies, the other methods including direct viable count, staining, and molecular biological methods have been used for differentiation between viable and dead cells (Schottroff et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, VBNC state of E. coli O157:H7 induced under high salinity stress in water microcosms and fish meat expressed all studied pathogenic genes including stx 1 , stx 2 , eae , and hly genes. Zolfaghari et al (2020) also reported the positive expression of pathogenic genes ( hly and inlA genes) of L. monocytogenes in the VBNC state (Zolfaghari et al, 2020). Although it has been reported that the expression of the pathogenic genes in VBNC state of bacteria does not necessarily indicate the production of toxins by these cells, VBNC related pathogenicity may be related to their rapid resuscitation in suitable situation (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wery et al, 2006;Klein et al, 2011;Maynaud et al, 2016;Afari and Hung, 2018 RT-PCR Reverse transcription polymerase chain reaction Detection of a messenger RNA (mRNA), by PCR amplification of a cDNA sequence synthesized from the mRNA template. Lindback et al, 2010;Zolfaghari et al, 2020 v-PCR (EMA-or PMA-qPCR) viability-PCR Ethidium monoazide (EMA) and propidium monoazide (PMA) are photoreactive DNA-intercalating dyes that, when used in combination with polymerase chain reaction, prevent the DNA of dead bacteria from being amplified. The dyes selectively enter only the compromised cells (PMA being more selective for dead cells than EMA).…”
Section: Overview Of the Vbnc Statementioning
confidence: 99%
“…Up to now, many studies have selectively examined the expression of key stress response and/or virulence genes in L. monocytogenes cells that have either grown in foods such as fruits and vegetables [16,17], cheeses [18], raw and processed meats [19][20][21][22], and fish [23], or have been exposed to low temperatures, acid and/or salinity stresses [24][25][26][27][28], or even in a simulated gastrointestinal environment [29,30]. Undoubtedly, all these studies have provided valuable information on the physiology and pathogenesis of that bacterium under some critical food-associated circumstances, revealing in some cases a worrying increase in pathogenicity following such habituation [31].…”
Section: Introductionmentioning
confidence: 99%